"A Giant Leap for Mankind" But What About Women? The Role of System-Justifying Ideologies in Predicting Attitudes Toward Sexist Language. (December 2014) - Douglas, Karen M.; Sutton, Robbie M.
Sexist language excludes, trivializes, or diminishes either gender. Despite efforts by many professional bodies to encourage the use of nonsexist alternatives, sexist language use persists across many languages. Furthermore, research has shown that men are less supportive of nonsexist language alternatives than women, and that this effect is mediated by attitudes toward women. We propose that broader ideologies related to the perceived legitimacy of dominance hierarchies and existing social systems also explain this gender gap. British undergraduate participants completed measures of attitudes toward women, gender-specific system justification, and social dominance orientation. They also completed an inventory of attitudes toward sexist language. There was a strong gender difference in attitudes toward sexist language that was significantly mediated by gender-specific system justification and social dominance orientation. The relationship between gender and attitudes toward sexist language therefore appears to be driven by broader ideologies that serve to keep women "in their place".